2021
DOI: 10.1007/s42768-021-00074-z
|View full text |Cite
|
Sign up to set email alerts
|

Review of low-temperature plasma nitrogen fixation technology

Abstract: Nitrogen fixation is essential for all forms of life, as nitrogen is required to biosynthesize fundamental building blocks of creatures, plants, and other life forms. As the main method of artificial nitrogen fixation, Haber–Bosch process (ammonia synthesis) has been supporting the agriculture and chemical industries since the 1910s. However, the disadvantages inherent to the Haber–Bosch process, such as high energy consumption and high emissions, cannot be ignored. Therefore, developing a green nitrogen fixat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 100 publications
0
35
0
Order By: Relevance
“…For most children with simple adenoid and/or tonsillar hypertrophy, adenoidectomy and tonsillectomy are the most effective treatment modalities, with an effective rate of up to 90%. Low-temperature plasma knife tonsil adenoidectomy performer is to ablate the adenoid tissue at a lower temperature in the ion field by the energy generated by low-temperature plasma radiofrequency [ 7 ], and the study [ 8 ] showed that low-temperature plasma surgery has the characteristics of light pain, small trauma, and quick postoperative recovery, and its tip has multiple functions such as flushing, hemostasis, and ablation. It does not need to change the instrument during operation, and it can be easily operated even if the oropharyngeal space is narrow.…”
Section: Prefacementioning
confidence: 99%
“…For most children with simple adenoid and/or tonsillar hypertrophy, adenoidectomy and tonsillectomy are the most effective treatment modalities, with an effective rate of up to 90%. Low-temperature plasma knife tonsil adenoidectomy performer is to ablate the adenoid tissue at a lower temperature in the ion field by the energy generated by low-temperature plasma radiofrequency [ 7 ], and the study [ 8 ] showed that low-temperature plasma surgery has the characteristics of light pain, small trauma, and quick postoperative recovery, and its tip has multiple functions such as flushing, hemostasis, and ablation. It does not need to change the instrument during operation, and it can be easily operated even if the oropharyngeal space is narrow.…”
Section: Prefacementioning
confidence: 99%
“…Electrochemical fixation of nitrogen (N 2 ) powered by renewable energy has emerged as a promising approach toward green ammonia synthesis alternative to conventional high energy-consuming , and CO 2 -emission Haber–Bosch process. Nevertheless, the high dissociation energy of NN (941 kJ mol –1 ) and the limited solubility of nitrogen in the aqueous solution lead to unacceptably low ammonia selectivity and productivity in electrochemical nitrogen fixation. , To overcome the intrinsic barrier of the direct electrolysis of N 2 , we recently proposed a “plasma-electrocatalysis” strategy by mimicking one of the natural nitrogen cycles, in which the nitrogen is first oxidized by non-thermal plasma to reactive nitrogen species (RNS) which is usually presented as water-soluble nitrate/nitrite species in aqueous electrolytes, and then, the produced RNS is converted into ammonia with a high selectivity and efficiency via electrochemical reduction. Therefore, it is keenly desired to develop highly selective and durable electrocatalysts for RNS reduction to ammonia.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of activation of an aqueous solution by low-temperature plasma, hydrogen peroxide and nitrate anion are generated at the plasma-solution interface [ 24 , 25 ]. These compounds have significant biological activity, impart antiseptic, and disinfecting properties to an aqueous solution [ 26 ], which is shown in the manuscript ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%